Fork PCR: a universal and efficient genome-walking tool - Pan, Hao; Guo, Xinyue; Pan, Zhenkang; Wang, Rongrong; Tian, Bingkun; Li, Haixing (Frontiers in Microbiology, 2023)
The reported genome-walking methods still suffer from some deficiencies, such as cumbersome experimental steps, short target amplicon, or deep background. Here, a simple and practical fork PCR was proposed for genome-walking. The fork PCR employs a fork primer set of three random oligomers to implement walking task. In primary fork PCR, the low-stringency amplification cycle mediates the random binding of primary fork primer to some places on genome, producing a batch of single-stranded DNAs. In the subsequent high-stringency amplification, the target single-strand is processed into double-strand by the site-specific primer, but a non-target single-stranded DNA cannot be processed by any primer. As a result, only the target DNA can be exponentially amplified in the remaining high-stringency cycles. Secondary/tertiary nested fork PCR(s) further magnifies the amplification difference between the both DNAs by selectively enriching target DNA. The applicability of fork PCR was validated by walking several gene loci. The fork PCR could be a perspective substitution for the existing genome-walking schemes.